National Gallery, Trafalgar Sqaure, London, and Royal Academy - Rogers, John; Allom, Thomas (Tufts Archival Research Center, 2008)
This illustration is from Charles Knight's "London," Vol. 6. This image was inserted by Edwin C. Bolles and is not found in the original.